Address Forms in Turkish Culture as a Reflection of Social Status - Goktepe, Fatma Tokoz (Richtmann Publishing, 2021)
The study concerned itself with forms of communication and address in Turkish culture and seeks to study how they are today regarding how they have been developed historically. Many variables determine how one addresses another and the reasons behind how that forms are chosen. It is known that what is culturally acceptable and deemed polite varies across many different cultures, although some patterns are identical regardless of the culture in which they are exhibited. For the study, a survey was conducted upon several Turkish individuals, and the findings were analysed to extract specific themes and similarities in answers. The analysis was conducted via the Colaizzi method, in which a seven-step process was used to determine themes and recurring branches of themes in subjective interviews. The findings were reported upon and determined to correlate with what has been reported in previous literature on Turkish culture concerning social norms, forms of address and politeness. Received: 10 September 2021 / Accepted: 12 October 2021 / Published: 5 November 2021